An audit comparing the reporting of staging MRI scans for rectal cancer with the London Cancer Alliance (LCA) guidelines. Issue 11 (November 2017) - Siddiqui, M.R.S.; Shanmuganandan, A.P.; Rasheed, S.; Tekkis, P.; Brown, G.; Abulafi, A.M.
Abstract: Background: This article focuses on the audit and assessment of clinical practice before and after introduction of MRI reporting guidelines. Standardised proforma based reporting may improve quality of MRI reports. Uptake of the use may be facilitated by endorsement from regional and national cancer organisations. Methods: This audit was divided into 2 phases. MRI reports issued between April 2014 and June 2014 were included in the first part of our audit. Phase II included MRI reports issued between April 2015 and June 2015. Results: 14 out of 15 hospitals that report MRI scans in the LCA responded to our audit proposal. The completion rate of key MRI metrics/metrics was better in proforma compared to prose reports both before (98% vs 73%; p < 0.05) and after introduction of the guidelines (98% vs 71%; p < 0.05). There was an approximate doubling of proforma reporting after the introduction of guidelines and workshop interventions (39% vs 65%; p < 0.05). Evaluation of locally advanced cancers (tumours extending to or beyond the circumferential resection margin) for beyond TME surgery was reported in 3% of prose reports vs. 42% in proformas. Conclusions: Incorporation of standardised reporting in official guidelines improved the uptake of proforma based reporting. Proforma based reporting captured more MRI reportable items compared to prose summaries, before and after the implementation of guidelines. MRI reporting of advanced cancers for beyond TME surgery falls short of acceptable standards but is more detailed in proforma based reports. Further work to improve completion especially in beyond TME reporting is required.